A pair of homochiral porous metal–organic frameworks with a helical metal-carboxylate layer. (24th December 2015) - Xu, Zhong-Xuan; Liu, Liyang; Zhang, Jian
Abstract : By employment of predesigned proline derivative ligands (( R )-PIA and ( S )-PIA) to assemble with bipy and Cd 2+ ion, a pair of porous homochiral metal–organic frameworks (HMOFs) with a wavy Cd-PIA layer has been synthesized. Abstract : A pair of porous homochiral metal–organic frameworks has been successfully synthesized from a proline-derived ligand and 4, 4′-bipyridine, which contain an interesting wavy helical metal-carboxylate layer.